Hemodynamic correlates of transient cognitive impairment after transient ischemic attack and minor stroke: A transcranial Doppler study - Mazzucco, S; Li, L; Tuna, M; Pendlebury, S; Wharton, R; Rothwell, P (SAGE Publications, 2016)
Background and Aims Transient cognitive impairment (TCI) on the Mini Mental State Evaluation (MMSE) score is common after TIA/minor stroke and might identify patients at increased risk of dementia. We aimed to replicate TCI using the Montreal Cognitive Assessment (MoCA), compare it with persistent Mild Cognitive Impairment (PMCI), and to determine whether global cerebral haemodynamic changes could explain transient impairment. Methods Consecutive patients with TIA/minor stroke (NIHSS≤3) were assessed with the MoCA and transcranial Doppler (TCD) ultrasound acutely and at 1-month. We compared patients with TCI (baseline MoCA <26 with ≥2 points increase at 1-month), PMCI (MoCA <26 with <2 points increase), and no cognitive impairment (NCI, MoCA ≥26). Results Of 326 patients, 46 (14.1%) had PMCI, 98 (30.1%) TCI and 182 (55.8%) NCI. At baseline, TCI patients had higher systolic blood pressure (150.95±21.52 versus 144.86±22.44 mmHg, p=0.02) and lower cerebral blood flow velocities, particularly end-diastolic velocity (EDV) (30.16±9.63 vs 35.02±9.01 cm/sec, p<0.001) and mean flow velocity (MFV) (48.95±12.72 vs 54±12.46 cm/sec, p=0.001) than those with NCI, but similar clinical and hemodynamic profiles to those with PMCI. Systolic BP fell between baseline and one-month (mean reduction=14.01±21.26 mmHg) and EDV and MFV increased (mean increase = +2.42±6.41 and 1.89±8.77 cm/sec respectively), but these changes did not differ between patients with TCI, PMCI and NCI. Conclusions TCI is detectable with the MoCA after TIA and minor stroke and has similar clinical and haemodynamic profile to PMCI. However, TCI does not appear to be due to exaggerated acute reversible global haemodynamic changes.